Pemanfaatan Teori Semantic Web pada Pengembangan Intelligent Learning Management System (ILMS) - Ahmad Luthfi (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2006)
This paper emphasizes integration of the Semantic Web technologies in intelligent learning systems by giving a method for an Intelligent Learning Management System (ILMS) architecture named Multitutor. This system is a Web-based environment for the development the e-Learning courses and for the use of them by the students. Multitutor is designed as a Web-classroom client-server system, ontologically founded, and is built using modern intelligent and Web-related technologies. This system enables the teachers to develop tutoring systems for any course. The teacher has to define the metadata of the course: chapters, the lessons and the tests set, and also the references of the learning materials.Keyword: Semantic Web, Learning Management System, Ontology